The effect of premarital sex counseling using jigsaw method on adolescent’s knowledge - Happy Imanisa Mahira; Anita Rahmawati; Yani Widyastuti (Poltekkes Kemenkes Yogyakarta, 2019)
The problem that stands out among adolescents is about the Three Problems of Adolescent Reproductive Health, one of which is premarital sex. The low level of knowledge about sexuality and reproductive health is one of the factors that influence the occurrence of premarital sex relations. One effort to provide reproductive health information for adolescents is to provide health promotion or counseling. Health counseling conducted in this study was the jigsaw. The objective was to know the influence of giving counseling with jigsaw compare to lecturer method on knowledge about premarital sex. This research was quasi-experiment research with pre-test and post-test nonequivalent control group design. The study was conducted in March 2019 in YPKK 1 and YPKK 2 Vocational School, Sleman. The sampling uses convenience sampling. The sample for each grup of this study amounted to 30 respondents. Data was analyzed using the Wilcoxon test and the Mann Whitney test. There was significant difference in the pre-test and post-test of adolescent’s knowledge about premarital sex with the jigsaw method (Mean difference= 14.66; p-value= 0.000) and lecture method (Mean difference= 6.00; p-value= 0.001). There was significant difference in knowledge changes of adolescent’s knowledge about premarital sex with the jigsaw method than lecture method (Mean difference= 19.84; p-value= 0.000). The jigsaw method was more effective on increasing knowledge of adolescent’s about premarital sex.